E-Chinese Language Learning - Quik, Sheue Ni (2007)
The use of internet is widespread in numerous fields and domains; it carries great potential for educational use, specifically second and foreign language education. This paper will therefore focus on the Chinese language learning and how does internet help in encouraging the learning process. In this paper, I will develop a Chinese e-learning portal which best help the learners in their Chinese language learning process.